Reproductive and lamb growth performance of Balami and desert Sudanese sheep in the Sahelo-Sudan savanna zone of Nigeria - Adu, I.F.; Taiwo, B.B.A.; Buvanendran, V. (1985)
Reports the comparative performance of indigenous Balami and imported Desert Sudanese sheep. The reproductive and growth performances of Balami and Sudanese Desert sheep were studied using 466 lambing record from 147 Balami and 126 Desert Sudanese ewes during 2-year period. The Balami was significantly (P